Three criteria for establishing the usefulness of biotechnology for reducing micronutrient malnutrition - Bouis, Howarth E. (SAGE Publications, 2002)
The fundamental reason that plant breeding using either conventional breeding or biotechnology is so cost-effective is that the benefits of a one-time investment at a central research location can be multiplied over time across nations all over the world. Supplementation and fortification incur the same recurrent costs year after year in country after country. However, each intervention has its own comparative advantages, such that a combination of several interventions is required to substantially reduce micronutrient malnutrition. Improving the density of trace minerals in plants also reduces input requirements and raises crop yields. A simulation model for India and Bangladesh demonstrated that $42 million invested in conventional breeding in developing and planting iron- and zinc-dense varieties of rice and wheat on only 10% of the acreage used for these crops would return $4.9 billion in improved nutrition (including a total of 44 million prevented cases of anemia over 10 years) and higher agricultural productivity.